Graphic chronicles of the full-scale Russian-Ukrainian war in the works of Ukrainian icon painters - Kendzor, Olena-Olha (Art and Design, 2026)
The relevance of the study was determined by the active dissemination of expressive graphic sketches created by artists during the full-scale war, a significant part of which combines the iconographic tradition with elements of war reporting. Despite the presence of these works in the digital space and the growing interest in them, the illustration of war crimes by Ukrainian icon painters is an understudied topic. The aim of the article was to outline the role of graphic chronicles in the works of Roman Barabakh, Ulyana Krekhovets and Danylo Movchan and to identify the artistic features of the works. The study used qualitative and quantitative methods, formal, iconographic, and semiotic analysis. It analysed 164 works created by Ukrainian icon painters during the full-scale war. The article focused on works created between March and July 2022, when icon painters were most active in creating graphic chronicles. The analysed works demonstrated a synthesis of the visual language of icon painting with the current political and social context. The artists’ work revealed active encryption of meanings through the symbolic system of iconography, the personification of heroes in the form of saints, references to local iconographic images, and the documentation of specific military events. The article noted a decrease in the number of such works, indicating the emotional exhaustion of artists and the gradual adaptation of society to the prolonged threat. The analysis showed that graphic chronicles created by icon painters during the war perform a number of important functions, including social, memorial, and communicative ones. In particular, it was found that social networks were actively used by artists to disseminate their work and engage the audience in reflection. The practical value of the study lay in recording new artistic strategies that demonstrated the transformation of iconographic images during wartime. The study of these processes provided a deeper understanding of the role of sacred art as a form of reflection, documentation and spiritual support in times of trial